2017
DOI: 10.1007/s00330-017-4999-1
|View full text |Cite
|
Sign up to set email alerts
|

Local recurrence of squamous cell carcinoma of the head and neck after radio(chemo)therapy: Diagnostic performance of FDG-PET/MRI with diffusion-weighted sequences

Abstract: PurposeTo determine the diagnostic performance of FDG-PET/MRI with diffusion-weighted imaging (FDG-PET/DWIMRI) for detection and local staging of head and neck squamous cell carcinoma (HNSCC) after radio(chemo)therapy.Materials and methodsThis was a prospective study that included 74 consecutive patients with previous radio(chemo)therapy for HNSCC and in whom tumour recurrence or radiation-induced complications were suspected clinically. The patients underwent hybrid PET/MRI examinations with morphological MRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 46 publications
1
47
0
1
Order By: Relevance
“…On the basis of the experience at our institution and according to published data, 1,14,15 the interpretation of morphologic MRI was performed according to the following criteria: 1) rHNSCC/ sHNSCC was diagnosed in the presence of a masslike lesion with moderately high (intermediate) signal intensity on T2, low signal intensity on T1, and moderate enhancement after IV gadolinium administration; 2) post-RTH inflammatory edema was diagnosed in the presence of a diffuse lesion with high signal intensity on T2, low signal intensity on T1, and strong postcontrast enhancement; and 3) late RTH fibrosis (post-RTH scar) was diagnosed in the presence of a linear or triangular lesion with very low signal intensity on T2 (similar to or lower than that of muscle), low signal intensity on T1, and faint/absent contrast enhancement. 1,14,15 DWI was assessed visually (qualitative DWI) by analyzing the signal intensity on the bϭ1000 image and on the corresponding ADC map. The association of moderately high or very high signal on bϭ1000 and low signal on ADC maps was interpreted as suggesting malignancy.…”
Section: Evaluation Of Morphologic Mri and Dwi And Applied Diagnosticmentioning
confidence: 99%
“…On the basis of the experience at our institution and according to published data, 1,14,15 the interpretation of morphologic MRI was performed according to the following criteria: 1) rHNSCC/ sHNSCC was diagnosed in the presence of a masslike lesion with moderately high (intermediate) signal intensity on T2, low signal intensity on T1, and moderate enhancement after IV gadolinium administration; 2) post-RTH inflammatory edema was diagnosed in the presence of a diffuse lesion with high signal intensity on T2, low signal intensity on T1, and strong postcontrast enhancement; and 3) late RTH fibrosis (post-RTH scar) was diagnosed in the presence of a linear or triangular lesion with very low signal intensity on T2 (similar to or lower than that of muscle), low signal intensity on T1, and faint/absent contrast enhancement. 1,14,15 DWI was assessed visually (qualitative DWI) by analyzing the signal intensity on the bϭ1000 image and on the corresponding ADC map. The association of moderately high or very high signal on bϭ1000 and low signal on ADC maps was interpreted as suggesting malignancy.…”
Section: Evaluation Of Morphologic Mri and Dwi And Applied Diagnosticmentioning
confidence: 99%
“…In a study demonstrating the multiparametric capabilities of PET/MRI, Becker et al showed excellent results for detection of recurrent disease and tumor classification of PET/MRI performed with diffusion weighted imaging (DWI) in the post-treatment setting. 42 This study notes the value of concordant imaging results between PET, MRI, and DWI in predicting tumor recurrence, and discordant results corresponding to benign post-treatment changes. 42 These results differ from an earlier study by Queiroz et al, which concluded that DWI was not helpful in the evaluation of head and neck malignancy with PET/MRI.…”
Section: Accepted Manuscriptmentioning
confidence: 82%
“…As an alternative to PET-CT, hybrid PET MRI provides robust multiparametric anatomic, functional and metabolic information while significantly reducing radiation exposure [ 12 16 ]. It also offers the possibility to accurately detect recurrent disease and to effectively follow patients in a non-invasive fashion by using a combined multiparametric approach once a malignant tumour has been identified [ 17 ].…”
Section: Imaging Techniquesmentioning
confidence: 99%